Analytical model for hybrid FRP-steel reinforced shear walls. (1st February 2018) - Ghazizadeh, Sina; Cruz-Noguez, Carlos A.; Talaei, Fereshte
Highlights: A useful FE model for analysis of FRP-reinforced shear walls is presented. Hybrid FRP-steel walls can achieve comparable strength and ductility with RC walls. The hybrid walls exhibit less residual displacements than RC walls under earthquakes. Abstract: Experimental studies showed that concrete shear walls reinforced exclusively with GFRP bars had satisfactory strength and stable cyclic behavior, making them suitable for use in areas with low seismic risk. However, in areas in which the lateral demands are higher, the GFRP reinforcement might be inadequate due to the brittle nature of the material, and its reduced energy dissipation capacity. In this study, a finite-element (FE) analysis model for hybrid GFRP-steel reinforced shear walls for moderate seismic demands was developed. The steel lent ductility to the system, while the GFRP material enhanced the self-centering ability of the wall to reduce permanent displacements. The analysis model was first validated with experimental results obtained from steel- and FRP-reinforced walls from literature, and then used to determine the most suitable hybrid scheme combining ease of construction, maximum ductility, and minimum residual displacements. It was shown that hybrid walls have comparable strength and ductility to conventional steel-reinforced shear walls, while having better self-centering capacity under lateral loads. Simplified nonlinear dynamic analyses were conducted to study the performance of hybrid systems subjected to four earthquakes. The response of RC and hybrid steel-FRP walls were shown to be comparable when designed properly in terms of stiffness and serviceability.